2017
DOI: 10.1007/s00705-017-3505-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of waterborne norovirus genogroup I strains using an improved real time RT-PCR assay

Abstract: Noroviruses (NoVs) are the major global source of acute gastroenteritis (AGE) outbreaks. To detect NoVs, real-time reverse transcription-quantitative PCR (RT-qPCR) assays have been widely employed since the first decade of the 21 century. We developed a redesigned probe, JJV1PM, for RT-qPCR assay detection of NoV genogroup (G) I strains. The new RT-qPCR assay using the JJV1PM-probe showed broader strain reactivity for 10 NoV GI genotypes, while the old method, using the JJV1PT-probe assay, detected only 7 NoV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The inability to identify NoV GI with qRT-PCR might be related to the mismatched base present in the forward primer sequence used for detection, but even without mismatches, primer-probe pairs can be improved to provide better detection. In a recent study, researchers designed an improved probe for NoV GI.2 strains, lowering the limit of detection for these strains from waterborne samples ( 47 ). It is, therefore, possible that the NoV GI.2 detected here with viromics methods was present below the limit of detection of the ISO standard primer/probe combination ( 48 ) used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to identify NoV GI with qRT-PCR might be related to the mismatched base present in the forward primer sequence used for detection, but even without mismatches, primer-probe pairs can be improved to provide better detection. In a recent study, researchers designed an improved probe for NoV GI.2 strains, lowering the limit of detection for these strains from waterborne samples ( 47 ). It is, therefore, possible that the NoV GI.2 detected here with viromics methods was present below the limit of detection of the ISO standard primer/probe combination ( 48 ) used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…While the known NoV GI.2 genotypes do not have a mismatch in the qRT-PCR probe sequence, it is possible that the genome recovered in this study fell below the limit of detection using the ISO standard primer/probe combination (ISO/TS 15216-2:2013). In a recent study, researchers designed an improved probe and observed lower Ct values and a lower limit of detection for GI.2 strains from waterborne samples (47). Viromics as a means of investigating water samples for the presence of norovirus, does have the advantage of demonstrating the presence of an undegraded genome, provided the sample processing requirements do not lead to excessive loss of virus particles resulting in false negatives.…”
Section: Discussionmentioning
confidence: 99%